2003
DOI: 10.1038/sj.thj.6200224
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of FLT3 ITD and D835 mutations in AML patients

Abstract: Both ITD and D835 mutations of the fms-like tyrosine kinase (FLT3) gene cause constitutive activation of the receptor, in the absence of ligand. We have examined a cohort of 91 patients, AML (80) and MDS (11), to determine the prevalence of these mutations and any correlations between the two mutations and disease prognosis. FLT3/ITD (ITD+) or D835 mutations (D835+) were not detected in MDS patients examined. However, 10% (8/80) and 7.5% (6/80) of AML patients were ITD+ and D835+, respectively. ITD+ patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 14 publications
8
50
3
Order By: Relevance
“…[9][10][11][12][13][14]24 Since TKD mutation enhances the proliferative activity of AML cells in vitro to the same level as ITD does, 24 TKD mutation may also have a prognostic value. In contrast with ITD, however, which is found in 20-30% of AML cases, the frequency of TKD mutation ranges from 5 to 10%, Figure 1 Forrest plots of the hazard ratios (HRs) and 95% confidence intervals for disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14]24 Since TKD mutation enhances the proliferative activity of AML cells in vitro to the same level as ITD does, 24 TKD mutation may also have a prognostic value. In contrast with ITD, however, which is found in 20-30% of AML cases, the frequency of TKD mutation ranges from 5 to 10%, Figure 1 Forrest plots of the hazard ratios (HRs) and 95% confidence intervals for disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] FLT3-ITD is found in 20-30% of patients with AML, and many studies have shown that its presence correlates with poor outcome. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] On the other hand, the prognostic relevance of TKD mutation is less clear. [9][10][11][12][13][14]24 Because of the relatively infrequent occurrence of TKD mutation, it can be assumed that a single study might be inadequate to accurately determine the effect of this mutation.…”
Section: Introductionmentioning
confidence: 99%
“…32,39 Mutations in the tyrosine kinase domain of FLT3 frequently occur in patients with prognostically favorable NPM1 mutations, which further complicates analyses of their impact on patient outcomes. 40,41 In fact, a study of 1107 adult patients with AML showed improved survival in patients with FLT3 tyrosine kinase domain mutations vs patients with wild-type FLT3.…”
Section: Flt3 As a Prognostic Markermentioning
confidence: 99%
“…Constitutive activation of the Flt3 receptor tyrosine kinase, either by internal tandem duplication (ITD) mutations of the juxtamembrane domain or point mutations clustering in the second tyrosine kinase domain (TKD mutations as D835), has been found in 20% to 30% of patients with AML and in 30% to 45% of patients with normal karyotype (reviewed by Stirewalt and Radich (2003)). ITD mutations have been associated with an increased risk of treatment failure after conventional chemotherapy (overall survival and disease-free survival were worse for ITD positive patients versus FLT3 wildtype patients), whereas the prognostic relevance of FLT3 point mutations is less evident (D835 mutants did not appear to have a worse median overal suvival or disease-free survival compared with the wildtype group) (Sheikhha et al, 2003). Recently, Spassov et al analyzed for WT1 and FLT3-internal tandem duplication (FLT3-ITD) expression in 30 samples of AML patients and determined that high WT1 expression correlated with the presence of FLT3-ITD (P = 0·014) and with a lower rate of complete remissions (P = 0·023) (Spassov et al, 2011).…”
Section: Flt3mentioning
confidence: 99%
“…This is particularly important in the case of patients with normal cytogenetics who comprise the largest subgroup of AML patients (approximately 45%) where many new prognostic factors have been identified. These include gene mutations in FLT3 (Fms-like tyrosine kinase 3; generally FLT3-ITD has been associated with significantly worse survival (Sheikhha et al, 2003)), NPM1 (nucleophosmin 1) and CEBPA (CCAAT enhancer-binding protein-α; generally favorable in cases of biallelic mutations) and gene overexpression as BAALC, WT1, EVI1 and MN1 (Foran, 2010). Identifying alterations in these genes might provide independent prognostic value in predicting the outcome of acute leukemia, as in the case of the NPM1 mutation gene, which is a relatively frequent abnormality in AML patients and is useful in detecting MRD (Falini et al, 2007).…”
Section: Genetic Alterations With Prognosis Valuementioning
confidence: 99%